2018
DOI: 10.1002/ejic.201800085
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Aqueous Synthesis of Propargylamines through C–H Activation Catalyzed by Magnetic Organosilica‐Supported Gold Nanoparticles as an Artificial Metalloenzyme

Abstract: Highly efficient magnetic organosilica-supported gold nanoparticles were developed as an artificial metalloenzyme for the synthesis of propargylamines through C-H activation in water under an ambient atmosphere. Herein, we present a very simple and efficient method for the deposition of Au nanoparticles on porous magnetic organosilica (Fe 3 O 4 @SiO 2 -Cl) through the thermal reduction of an organometallic Au III complex. As a nucleophile, a Au III polypyridyl coordination complex could react with alkyl halide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…In 2018, Aghahosseini et al. disclosed their report on the synthesis of propargylamine using magnetic organosilica‐supported Au‐NPs (Au@SiO 2 ‐Cl@Fe 3 O 4 ) [152] . They reported the synthesis via C−H activation of phenylacetylene.…”
Section: Functionalization Of C−h Bond Via C−h Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Aghahosseini et al. disclosed their report on the synthesis of propargylamine using magnetic organosilica‐supported Au‐NPs (Au@SiO 2 ‐Cl@Fe 3 O 4 ) [152] . They reported the synthesis via C−H activation of phenylacetylene.…”
Section: Functionalization Of C−h Bond Via C−h Activationmentioning
confidence: 99%
“…With the great advance, considerable recent progress has been achieved in the development of support materials for supported NPs based heterogeneous catalysts. The majority of the support materials are silica [15–21] metal‐oxides [22–30] carbon‐based materials [31–36] and metal‐organic frameworks (MOFs) [37–40] . It has been reported that the catalytic activities of supported metal NPs catalysts can be tuned using a variety of metal‐support interaction types [10,41] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, copper(0) FS and copper(II) FS are the efficient catalysts in A 3 coupling and C−N coupling reactions, respectively. Gold(0) FS and gold(I) FS catalysts are used to promote A 3 coupling and Suzuki cross coupling reactions, respectively. While iron(III) FS catalyst is useful in the cross‐coupling reaction between olefins and aryl iodides, nickel(II) FS catalyst promotes the Kumada‐Corriu reaction .…”
Section: Applications and Advantages Of Fs‐based Catalystsmentioning
confidence: 99%
“…Nanomaterials may also be endowed with specific additional properties that enhance their applicative interest. For example, when MNPs are employed as photocatalysts [ 44 , 45 ], light-activation can promote the single electron transfer mechanism (SET), or alternatively, NPs with magnetic properties can be separated from the reaction mixture, simplifying product isolation [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%